Vaginal examination does not improve diagnostic accuracy in early pregnancy bleeding. (1st April 2013) - Johnstone, Chris
Abstract Objective The study aims to determine if a vaginal examination improves diagnostic accuracy when assessing women who present to the ED with vaginal bleeding in the first trimester of pregnancy. Methods One hundred and thirty‐five women with first trimester bleeding were randomised to have a vaginal examination (n = 61) or not (n = 74). They were given a provisional diagnosis, and then a final diagnosis after ultrasound, beta‐human chorionic gonadotropin and gynaecological follow up. The provisional diagnosis was considered accurate if it matched the final diagnosis. Results The provisional and final diagnoses matched in a little over half of the cases, and there was no statistical difference between the two groups (χ2 = 0.005, P = 0.94). Conclusion In a stable patient presenting to the ED with first trimester bleeding, clinical diagnosis is highly inaccurate and is not improved by vaginal examination. Routine vaginal examination is not necessary as part of the initial patient assessment.